Fisheries geographical information system for Greater Mumbai region in Maharashtra, India - Ghatge, Swapnil Shivajirao; Biradar, R. S.; Pawar, N. A.; Chaudhary, A. K. (Indian Journal of Fisheries, 2015)
Geographical information system (GIS) is an invaluable decision support tool, designed to address spatially related problems for management of natural resources. The power of GIS lies in its ability to visualise and relate various types of geo-referenced spatial and non-spatial data allowing users to analyse them. In India, use of GIS in fisheries management is yet to find its rightful place. An effort has been made in the present study to design and organise a fisheries spatial information system for Greater Mumbai region in Maharashtra to serve as a macro-level database for the planners and administrators, which can be used for querying, analysing and displaying datasets in the form of graphs and summarised tabular data for all the fisheries infrastructural facilities. This GIS will be of immense help to planners, managers and administrators in quick storing, retrieving and updating the required information for management of fisheries in Greater Mumbai region.